LEVEL SOFT GROUP AND ITS PROPERTIES - Abdurrahman, Saman; Idris, Mochammad; Faisal, Faisal; Hijriati, Na’imah; Thresye, Thresye; Lestia, Aprida Siska (BAREKENG: Jurnal Ilmu Matematika dan Terapan, 2025)
In this paper, we present an application of fuzzy subset and fuzzy subgroup to a soft set and a soft group, thereby creating a soft set and a soft group within the same group. Furthermore, we refer to the soft and soft groups as level soft sets and level soft groups. We also found out the level of soft sets and the operations on soft sets, such as intersection, union, and subset. We also examine what conditions a fuzzy subgroup and a soft group must meet to form a level soft group. Moreover, we scrutinize the properties of operations on a soft set, specifically intersection, union, and AND, and apply them to the level soft group to ascertain if they consistently produce a level soft group over the same set. Furthermore, we investigate the formation of a level soft and level soft group resulting from the homomorphism of the group and soft group. The research findings can enrich studies on the relationships between structures in fuzzy subgroups and soft groups and the application of soft group levels in further research.